MORPHOLOGICAL AND GENETIC CHARACTERISATION OF DOMESTICATED GUINEA FOWL IN SOKOTO STATE, NIGERIA (2014)
Breed characterisation establishes genetic variability of organisms in a population which remains the basis for genetic improvement. Although, most poultry species have been largely characterised, little emphasis has been placed on domesticated Guinea fowl in Nigeria. Therefore, morphological and genetic characterisation of domesticated Guinea fowl was undertaken in Sokoto state, where there is a substantial population of the birds in Nigeria. Guinea fowl varieties aged between 30 and 40 weeks: 425 pearl; 313 lavender; 271 black and 263 white were randomly selected from smallholders in Sokoto, Balle, Bodinga, Shagari, Goronyo, and Illela villages. Body Weight (BW), Head Thickness (HT), Helmet Length (HL), Helmet Width (HW), Wattle Length (WL), Wattle Width (WW), Keel Length (KL), Body Circumference (BC), Shank Length (SL), Shank Thickness (ST), Drumstick Length (DL), Thigh Length (TL) and Wing Length (WGL) were measured using standard procedures. Blood (5mL) samples were drawn by wing venipuncture from 50 randomly selected birds from each of the varieties for genetic studies. The blood samples were subjected to Cellulose Acetate Electrophoresis to determine genetic polymorphisms at haemoglobin, transferrin and Carbonic Anhydrase (CA) loci using standard procedures. Data were analysed using descriptive statistics, correlation, discriminant analysis, Principal Components Analysis (PCA), Euclidian distance, heterozygosity, Hardy-Weinbergs Equilibrium and ANOVA at ?0.05. The BW (kg) were 0.940.01, 0.930.01, 0.870.04 and 0.870.03 while HT (cm) were 0.320.00, 0.280.00, 0.270.01 and 260.01 for pearl, lavender, black and white varieties, respectively. The BW, HT, HL and WW differed between lavender and pearl varieties while KL was similar. However, WL and WGL differed among varieties. There was strong relationship between BW and TL (r=0.95), BW and BC (r=0.94), HL and WW (r=0.97), and BC and WL (r=0.96) for pearl, lavender, black and white Guinea fowl, respectively. The most discriminating of the birds morphology was SL (0.9) followed by WGL (0.7), HW (0.6) and HT (0.5). Three PCA: PC1, PC2 and PC3 were extracted for lavender, PC1 and PC2 each for pearl and black and PC1 for white. The first factor explained 77.4, 61.2, 67.1, and 84.2 % of the generalised variance in pearl, lavender, black and white varieties respectively. The genetic distance between pearl and black (70.7) was highest and least between white and black (5.4) varieties. The allele frequencies of haemoglobin A and B were 0.96 and 0.04 in pearl, 0.95 and 0.05 in lavender, 0.96 and 0.04 in black and 0.95 and 0.05 in white varieties. Two haemoglobin genotypes (AA and AB) were noticed in each of the four varieties. The transferrin (TfA) and CA (CAF) were monotypic in all the varieties. The dendogram clustered all the varieties as two homogenous groups. The Chi-squared (?2) values showed departure from Hardy-Weinbergs Equilibrium in pearl (?2=62.0), lavender (?2=66.0), black (?2=39.0) and white (?2=39.0) varieties. Morphologically, the pearl variety of Guinea fowl was superior to others. Biochemical parameters revealed high genetic similarities among the varieties. However, there is possibility of genetic improvement among the varieties through cross breeding.